A survey of compassion satisfaction, burnout and compassion fatigue in nurses practicing in three oncology departments in Durban, South Africa - D.L. Wentzel; P. Brysiewicz (Elsevier, 2018)
Purpose: Prolonged and continual contact with grief and recurrent deaths, observing patients undergoing unrelenting medication therapies which could prove unsuccessful, and a constant atmosphere of hopelessness put the oncology nurse at high risk of developing compassion fatigue and burnout. This study conducted a survey of compassion satisfaction, burnout and compassion fatigue in nurses practicing in three oncology departments in Durban, South Africa. Method: A quantitative non-experimental descriptive survey using purposive sampling. Results: Results revealed that 55% (n = 83) of participants had high compassion satisfaction, 61% (n = 83) had average burnout and 75% (n = 83) had average compassion fatigue. Only three participants scored high risk for compassion fatigue. Conclusions: The results from this study are in contrast to previous international and national studies where compassion fatigue and burnout were reported at high-risk levels. This study revealed average to high levels of compassion satisfaction. Keywords: Compassion fatigue, Burnout, Compassion satisfaction, Oncology nurses